Device-Free Mobile Target Tracking Using Passive Tags - Han Ding; Min Xi; Zhe Li; Jizhong Zhao (International Journal of Distributed Sensor Networks)
We propose a low-cost device-free mobile target tracking system using passive tags, namely, DTrack, to detect and track a human object in a certain surveillance area. The idea is that when a human object moves, he may block or reflect the RF signals between the reader and tags. Based on the estimation of Doppler Shift and Tag Read Rate variations, DTrack can detect whether a human object enters in the system and further track the moving direction of the object. DTrack uses commercial readers and off-the-shelf passive tags and is scalable and easy for large-scale deployments. Experimental results show that our system is effective in detecting the direction of moving human objects with high accuracy.